Planning and assigning tasks for the first time: A step by step approach for beginning managers. - A.G.B. Simime (Research, Information and Publications Department, 2025)
Planning and assigning tasks for the first time a step by step approach for beginning managers. The bottom line of performance management is better results, hence, management by results. What it means really is that the performance of the manager is measured by the degree of success towards expected outputs or results. Successful performance reaches stated goals, objectives and targets and demonstrates visible and measurable contributions to an organization There are no magical rules for performance management. There are, however, process steps that managers ought to know that are likely to inspire effective commitment of the people to their jobs. If these process steps are followed management by results will be ensured. This small volume describes the eight step-by-step approach to assigning tasks as part of implementing performance management. The book outlines what managers who assign tasks to subordinates ought to do at each of the eight process steps in order to establish understanding, win their agreement and inspire their commitment to work for better results. At the end the book provides cases of success stories in planning and assigning task.